Associations Between Job-Strain, Physical Activity, Health Status, and Sleep Quality Among Swedish Municipality Workers - Leitaru, Naimi (J Occup Environ Med, 2019)
OBJECTIVE: To examine the associations between work-stress and physical activity (PA) with sleep quality while controlling for covariates, including social support. METHODS: A cross-sectional study among employees of a municipality (n = 2765). Data from respondents (n = 1973) with good/poor sleep quality were included. Prevalence ratios (PR) were estimated using modified Poisson regression analyses. RESULTS: A significant interaction was observed between job-strain and self-reported health in the explanation of sleep quality. Consequently, interaction (job strain × self-rated health) adjusted PRs were calculated. The PRs for high job strain were 1.986 (95% CI 1.58 to 2.49) and 1.220 (95% CI 1.04 to 1.44) compared with the reference groups. CONCLUSIONS: Findings show that high job strain and low PA levels are associated with poor sleep quality, and that self-rated health plays an important moderating role in the association between job strain and sleep quality.